1990
DOI: 10.1183/09031936.93.03020202
|View full text |Cite
|
Sign up to set email alerts
|

Metal toxicity and the respiratory tract

Abstract: The type of lung disease caused by metal compounds depends on the nature of the offending agent, its physicochemical form, the dose, exposure conditions and host factors. The fumes or gaseous forms of several metals, e.g. cadmium (Cd), manganese (Mn), mercury (Hg), nickel carbonyl (Nl(CO)4, zinc chloride (ZnCl2), vanadium pentoxide (V2O5), may lead to acute chemical pneumonitis and pulmonary oedema or to acute tracheobronchitis. Metal fume fever, which may follow the inhalation of metal fumes e.g. zinc (Zn), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(24 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…In our current study, several chemical constituents of PM 2.5 correlated with poorer respiratory outcomes and some had associations across multiple outcomes (Br, Ca, Fe, Mn, Pb, Si, and Zn). Although exposure to metal dust or fumes can cause serious cardiopulmonary complications (Bergström, 1977;Merget et al, 2002;Nemery, 1990;Woolf and Shannon, 1999;Zhou et al, 2018), these chemicals as particulate matters may have different mechanisms involved in their hazardous effects. The adverse health effects of PM 2.5 exposure are considered to be mediated by oxidative stress through the generation of reactive oxygen species, in ammation, and mitochondrial damage (Thangavel et al, 2022), with some PM 2.5 constituents sharing similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, several chemical constituents of PM 2.5 correlated with poorer respiratory outcomes and some had associations across multiple outcomes (Br, Ca, Fe, Mn, Pb, Si, and Zn). Although exposure to metal dust or fumes can cause serious cardiopulmonary complications (Bergström, 1977;Merget et al, 2002;Nemery, 1990;Woolf and Shannon, 1999;Zhou et al, 2018), these chemicals as particulate matters may have different mechanisms involved in their hazardous effects. The adverse health effects of PM 2.5 exposure are considered to be mediated by oxidative stress through the generation of reactive oxygen species, in ammation, and mitochondrial damage (Thangavel et al, 2022), with some PM 2.5 constituents sharing similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mn, a known neurotoxicant, would originate from the welding electrode and base metals and could act as a deoxidizing agent to increase the strength of the resultant weld [ 61 ]. A population-based study showed that Mn in welding fume and aging might make welders more susceptible to Alzheimer’s disease or related disorders [ 62 ]. In comparison, Zn may be derived from anti-rust painting on pipeline surfaces and additives to welding fillers of electrodes or materials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, highintensity, brief exposure to iron dust can also result in future symptoms [98]. It is important to realize that exposure to silica or asbestos is not uncommon in many jobs involving iron exposure, thus giving rise to mixed dust fibrosis or to asbestosis, which has associated morbidity and complications [99].…”
Section: Siderosismentioning
confidence: 99%
“…However, atypical radiologic findings rarely appear, which may be misdiagnosed as other diseases [100]. In addition, with the cessation of exposure, the radiographic opacities may gradually disappear [99]. At the time of welding, the aspirated iron oxide is stored in alveolar macrophages and then transferred to the lung parenchyma.…”
Section: Siderosismentioning
confidence: 99%